Pengaruh Lingkungan dan Gaya Hidup Hedonisme terhadap Manajemen Keuangan Pribadi Mahasiswa di Kota Medan - Sari, Nonik Widiya; Tanjung, Ahmad Albar (Universitas Proklamasi 45, 2024)
Personal financial management includes financial management, the process by which an individual ensures his or her needs are met. The purpose of this study is to determine the influence of environment and hedonistic lifestyle on student’s financial management. This research method uses Partial Least Squares (PLS) for analysis in this study. This research was conducted in 9 universities in Medan City with a sample of 164 students—data collection techniques by observation and questionnaire. The data source in this study is primary data in the form of research data and secondary data in the form of data sourced from parties outside this study. The study found that the environment has a positive and significant influence on student’s financial management and significant influence on personal financial management. The environment and lifestyle of hedonism must be managed in a balanced manner so it can give a good impact on financial management.